Upaya Tenaga Kependidikan Dalam Mengelola Sumber Daya Sekolah di Madrasah Ibdtidayah Negeri Kota Lhokseumawe - Marwansyah, Marwansyah; Alwi, Said; Yuliza, Yuliza (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze and describe the planning, implementation, and evaluation of educational staff resource management in improving performance professionalism at MIN Lhokseumawe. This research method uses a qualitative descriptive approach by analyzing the research results descriptively. The results of the study indicate that planning in education occupies a strategic position in the entire education process. The planning provides clarity of direction in the process of organizing education, so that planning in education can be implemented more effectively and efficiently. Also, the supervision and evaluation carried out on educational staff at MIN Lhokseumawe is good, seen from the supervision and evaluation carried out by the head of the Madrasah every time and every day on a periodic basis.